Barnāmaj al-Rūḥānīyah al-Islāmīyah wa al-Ḥayat al-Dīnīyah fī al-Madāris al-Thanāwīyah al-‘Āmmah fī Indūnīsīyā - Burhanudin, Jajat; Sulaiman, Setyadi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2010)
This article tries to portray the development of religious orientation in schools through a thorough investigation of the emergence of ROHIS in senior high schools and perusing its dynamics. After having been introduced in the mid-1980s, ROHIS has attracted many people. In the beginning it merely supported religious activities in schools, but gradually its importance became undeniable. Its significant contributions in endowing students with additional religious knowledge made ROHIS a well-recognized organization amongst students and teachers.DOI: 10.15408/sdi.v17i1.470